Sustainable Education Management Frameworks for Advancing Teacher Excellence and Educational Innovation - Iin Indra Nuraeni; Neni Utami Adiningsih; Riska Irnawati; Erni Furwanti; Reni Marlina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines sustainable education management frameworks aimed at enhancing teacher excellence and promoting educational innovation. A qualitative literature-based approach was applied through the synthesis of recent studies on strategic management, teacher development, and innovation in education. The findings indicate that sustainability-oriented management integrating adaptive leadership, continuous professional development, and digital transformation strengthens teacher competence and institutional innovation capacity. Collaborative governance and policy alignment are identified as key factors supporting long-term effectiveness. The study emphasizes the need for flexible yet consistent frameworks to address dynamic educational challenges. The results offer insights for developing context-sensitive strategies to improve teacher quality and support innovation in education systems.